2010
DOI: 10.1038/nsmb.1916
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of RAD51 recombinase activity by the tumor suppressor PALB2

Abstract: Homologous recombination mediated by the RAD51 recombinase helps eliminate chromosomal lesions, such as DNA double-stranded breaks induced by radiation or arising from injured DNA replication forks. The tumor suppressors BRCA2 and PALB2 act together to deliver RAD51 to chromosomal lesions to initiate repair. Here we document a new function of PALB2 in the enhancement of RAD51's ability to form the D-loop. We show that PALB2 binds DNA and physically interacts with RAD51. Importantly, while PALB2 alone stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
149
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 23 publications
5
149
0
2
Order By: Relevance
“…Together with BRCA2, the PALB2-BRCA2 heterodimeric complex initiates high-fidelity homologous recombination (HR) 4 DNA repair by promoting the assimilation of the recombinase RAD51 onto resected 3Ј single-strand overhangs (1)(2)(3). Inactivation of PALB2 compromised RAD51 loading onto DNA breaks, greatly diminished HR repair, and hyper-sensitized cells to genotoxic stress (4,5).…”
mentioning
confidence: 99%
“…Together with BRCA2, the PALB2-BRCA2 heterodimeric complex initiates high-fidelity homologous recombination (HR) 4 DNA repair by promoting the assimilation of the recombinase RAD51 onto resected 3Ј single-strand overhangs (1)(2)(3). Inactivation of PALB2 compromised RAD51 loading onto DNA breaks, greatly diminished HR repair, and hyper-sensitized cells to genotoxic stress (4,5).…”
mentioning
confidence: 99%
“…RAD51 is the central recombinase in HR, and it participates in D-loop formation and strand displacement (2). PALB2 also plays a BRCA2-independent role in the HR process by enhancing RAD51 function (3,4).…”
mentioning
confidence: 99%
“…3). Other biochemical studies showed that PALB2 binds DNA via two separate regions in the N-terminus of the protein, called PALB2 truncation 1 (P2T1) and PALB2 truncation 3 (P2T3), respectively (29,30). Particularly, P2T3 contains an evolutionarily conserved PALB2 motif, named chromatin-association motif (ChAM), which is figure 2.…”
Section: Discussionmentioning
confidence: 99%